2019
DOI: 10.7759/cureus.6307
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Syndrome in the Emergency Department

Abstract: With the widespread use of serotonergic agents including many antidepressants, antiemetics, illicit drugs, and even some herbal supplements, serotonin syndrome is a condition seen more frequently. It can appear abruptly and, if untreated, can progress to a life-threatening state. Prompt recognition and treatment is imperative to avoid complications. The presentation is variable and can be confused with other conditions. The authors present a case of serotonin syndrome that was recognized early and treated prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…It is speculated that drugs that modify 5-HT activity may have an inhibitory effect on LID. However, they require careful administration because an overdose of serotonin agonists leads to 5-HT syndrome, the symptomatology of which is similar (tremor and rigidity) to PD [ 120 ]. The 5-HT1A partial agonist buspirone inhibits LID in rats by influencing the 5-HT1A receptors, although it does not alter STN electrical activity [ 121 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is speculated that drugs that modify 5-HT activity may have an inhibitory effect on LID. However, they require careful administration because an overdose of serotonin agonists leads to 5-HT syndrome, the symptomatology of which is similar (tremor and rigidity) to PD [ 120 ]. The 5-HT1A partial agonist buspirone inhibits LID in rats by influencing the 5-HT1A receptors, although it does not alter STN electrical activity [ 121 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that modification of the serotonergic system exerts an inhibitory effect on LID. However, careful administration is required as an overdose of serotonergic agonists can lead to symptomatology (5-HT syndrome), which shows PD-like symptoms ( Hernandez et al, 2019 ). Buspirone, a partial 5-HT1A receptor agonist, was examined to be preventing the development of LID in rats without altering the STN electrical activity.…”
Section: Approaches For Management Of Levodopa-induced Dyskinesia: Pr...mentioning
confidence: 99%
“…It is speculated that drugs that modify 5-HT activity may have an inhibitory effect on LID. However, they require careful administration because overdose of serotonin agonists leads to 5-HT syndrome, symptomatology similar (tremor and rigidity) to PD [113]. The 5-HT1A partial agonist buspirone inhibits LID by influencing the 5-HT1A receptors, although it does not alter STN electrical activity [114].…”
Section: Serotonin In the Treatment Of Lidmentioning
confidence: 99%